Balún-Canán - Castellanos, Rosario (Colección popular (Fondo de Cultura Económica (Mexico)), 2010)
This novel, written by one of Mexico's most famous modern poets, illustrates many of the issues present in Mexico after the revolution. The story follows the life of a young girl growing up in Chiapas after the revolution and the politics surrounding the change of power.